Aliovalent ions substituted hydroxyapatite coating on titanium for improved medical applications. (2018) - Karthika, A.
Abstract: Currently, more prospects towards the quality of life have resulted in an increasing global demand for orthopedic implants to replace or repair damaged bones and joints. In which, hydroxyapatite is applied for the repair of bone defects with the substitution of trace amount of essential mineral ions into synthetic hydroxyapatite, since it is so tolerant to the ionic substitutions such as divalent and trivalent cations. The present work deals with the development of lanthanum and copper substituted hydroxyapatite (La/Cu-HAP) coating on titanium by electrodeposition method. The resultant coatings were characterized by Fourier transform infra-red spectroscopy, X-ray diffraction and scanning electron microscopy. The biological properties of La/Cu-HAP coating reveal that the developed material has good biocompatibility and bioactivity which finds its application in the field of orthopedics.